Intellectual capital on zakat performance with corporate governance as an intervening variable in sharia commercial banks - Wahyudi, Tri Wahyudi; Puspita, Gita (Jurnal Ekonomi & Keuangan Islam, 2022)
Purpose – This study aims to analyze the influence of intellectual capital; and corporate governance on the performance of zakat in Islamic commercial banks. Methodology – Population in this study is Islamic commercial banks registered in the Bank Indonesia database with the period spanning from 2014 to 2019. The samples were filtered using purposive sampling technique based on financial statement data. Analyses were carried out using classical assumption test and multiple linear regression analysis. Findings – The results from multiple linear regression analysess indicate that intellectual capital significantly influences zakat performance at 5 percent alpha level. However, intellectual capital has no effect on zakat performance when variable of corporate governance is treated as an intervening variable. Implications – This research can be used in the future both as a literature review and as a reference material that can be used by zakat institutions, Islamic banking, and the government, especially in Indonesia in managing and determining strategies to improve future company performance. Originality – In general, research using sharia principles for each variable calculation (iB-VAIC and Zakat) are still limited. In addition, there is only a few researchers who use the corporate governance variable as an intervening variable.